The Study of Australian Government Policies on Maqasid al-Sharia Perspective - M. Noor Harisudin (Justicia Islamica, 2021)
This article discusses the Australian government policies from the perspective of Maqasid al-Shari’a. The performance of policies focusing on the study is traffic laws, taxes, the environment, and anti-domestic violence. In several literature pieces, Maqasid al-Shari’a is defined as the purpose, objective, and secret set by Allah SWT in every Sharia law. Maqasid al-Shari’a is “Allah's goal (Shari) in making law.” In addition to being ”˜ammah (general), khassah (unique), and juz’iyah (parts), in Islam, Maqasid al-Shari’a is based on five main points as follows: protecting religion, protecting the soul, protecting reason, protecting property, and protecting descendants. After conducting in-depth interviews with several informants, books, and journals and tracing the laws on traffic, tax, environment, and anti-domestic violence in Australia, the conclusion is that the Australian government policies are based on Maqasid al-Shari’a in one part. However, it is not a country based on religion or Sharia, in the other part. Australia is a liberal country providing freedom for its citizens to have faith or no belief. However, in several other respects, it appears that the Australian government’s policies are against the Maqasid al-Shari’a, such as the ability to drink heavily in limited spaces, the life of same-sex marriages, and so on. This article is critical in developing policy studies of non-Islamic countries from the Maqasid al-Shari’a perspective.